2008
DOI: 10.1124/mol.107.040105
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Active and Inactive Phospholipase D2 on Signal Transduction, Adhesion, Migration, Invasion, and Metastasis in EL4 Lymphoma Cells

Abstract: The phosphatidylcholine-using phospholipase D (PLD) isoform PLD2 is widely expressed in mammalian cells and is activated in response to a variety of promitogenic agonists. In this study, active and inactive hemagglutinin-tagged human PLD2 (HA-PLD2) constructs were stably expressed in an EL4 cell line lacking detectable endogenous PLD1 or PLD2. The overall goal of the study was to examine the roles of PLD2 in cellular signal transduction and cell phenotype. HA-PLD2 confers PLD activity that is activated by phor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
65
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 44 publications
4
65
0
Order By: Relevance
“…In addition, actin polymerization and stress fiber formation are tightly coupled to the activation of PLD (14). The formation of lamellipodium structures and membrane ruffles is blocked by PLD inhibition (53,60), and PLD activity is critical for epithelial cell, leukocyte, and neutrophil adhesion and migration (41,43,52). Furthermore, we have previously shown that the activity of PLD is upregulated, and that the activated PLD is translocated to lamellipodia, after integrin activation (3).…”
mentioning
confidence: 98%
“…In addition, actin polymerization and stress fiber formation are tightly coupled to the activation of PLD (14). The formation of lamellipodium structures and membrane ruffles is blocked by PLD inhibition (53,60), and PLD activity is critical for epithelial cell, leukocyte, and neutrophil adhesion and migration (41,43,52). Furthermore, we have previously shown that the activity of PLD is upregulated, and that the activated PLD is translocated to lamellipodia, after integrin activation (3).…”
mentioning
confidence: 98%
“…PA mediates chemotaxis, as increasing concentrations of PA enhanced the rate of cell migration of phagocytes (35). In the murine lymphoma cell line EL4, Knoepp et al found that activated PLD2 promotes phosphorylation of FAK and Akt, leading to cell-substrate adhesion (7,29). However, while inactivated PLD2 inhibits adhesion, migration, proliferation, and tumor invasion, it does not alter the basal level of FAK and Akt phosphorylation (29).…”
mentioning
confidence: 99%
“…In the murine lymphoma cell line EL4, Knoepp et al found that activated PLD2 promotes phosphorylation of FAK and Akt, leading to cell-substrate adhesion (7,29). However, while inactivated PLD2 inhibits adhesion, migration, proliferation, and tumor invasion, it does not alter the basal level of FAK and Akt phosphorylation (29). Although PA does play a role in cell migration, the specific mechanisms involved are not completely understood, and more precise structurefunction studies are needed.…”
mentioning
confidence: 99%
“…PLD is upregulated at the protein and/or activity levels in various cancers, including breast, colon, gastric, kidney, and thyroid cancer (6). Overexpression of PLD isozymes has been reported to induce anchorage-independent growth, tumor cell invasion, and the formation of metastases in syngeneic mice (7,8). Significant correlation of PLD2 expression levels with tumor size and patient survival in colorectal carcinoma has been reported by recent clinical studies (6).…”
Section: Phospholipase D and Cancermentioning
confidence: 97%